The Relation between Sports Participation and Academic Achievement: The Mediating Role of Parental Support and Self-Esteem - Qurban, Haroona; Siddique, Hassan; Wang, Jin; Morris, Tony (Journal of Human Psychology, 2018)
Sports participation reported in a positive relationship with health and academic achievement. Sports participation may improve cognitive health leading to improved academic achievement. Some other factors may also be involved in this regard including parental support and self-esteem. In this study, we examined the relationship between sports participation, parental support, self-esteem and academic achievement due to concern about reduced education level of students and serious lack of research regarding this issue in Pakistan. We hypothesized that sports participation would influence students’ academic achievement. We further conceptualized a mediation model in which sports participation enhanced academic achievement through enhancing parental support and self-esteem. 248 students from three universities of Pakistan (male = 188; mean age = 17.5, SD = 1.15; female = 60; mean age =17.3, SD = 1.18) participated in the study, in which questionnaires were used to measure parental support, sports participation, and self-esteem. Two scales were used to measure parental support (school based parental support and sports participation based parental support). Sports participation level was measured using an adapted version of The Physical Activity Index (PAI) Scale consisting of 3 items. Rosenberg self-esteem scale assessed self-esteem. Data analysis was performed using the structural equation modelling.We found no direct relationship between sports participation and academic achievement. We found parental support and self-esteem as mediators in the relationship between sports participation and academic achievement. The mediational models suggested focus on vital role of parental support and self-esteem to have better academic performance.
Keywords: Sports participation; Parental support; Self-esteem; Academic achievement.